2013
DOI: 10.1002/chem.201302420
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Dynamics on the Molybdenum Carbide Surface during Catalytic Propane Dehydrogenation

Abstract: The effect of the gas-phase chemical potential on surface chemistry and reactivity of molybdenum carbide has been investigated in catalytic reactions of propane in oxidizing and reducing reactant mixtures by adding H2, O2, H2O, and CO2 to a C3H8/N2 feed. The balance between surface oxidation state, phase stability, carbon deposition, and the complex reaction network involving dehydrogenation reactions, hydrogenolysis, metathesis, water-gas shift reaction, hydrogenation, and steam reforming is discussed. Raman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Most of these states are distinct from the oxidation state of Mo in the parent Mo 2 C phase (+2) and should appear in experimental XPS spectra. Mo (3d) peaks in XPS studies are often assigned to oxidation states between +3 and +6, although it is difficult to determine accurately whether these species are due to an oxycarbide phase or to coexisting Mo oxide phases. …”
Section: Resultsmentioning
confidence: 99%
“…Most of these states are distinct from the oxidation state of Mo in the parent Mo 2 C phase (+2) and should appear in experimental XPS spectra. Mo (3d) peaks in XPS studies are often assigned to oxidation states between +3 and +6, although it is difficult to determine accurately whether these species are due to an oxycarbide phase or to coexisting Mo oxide phases. …”
Section: Resultsmentioning
confidence: 99%
“…Although most reports typically model Mo 4+ as one set of doublet peaks, 38,39 recent surface science literature has shown that Mo 4+ actually consists of 2 pairs of doublets with one narrow, asymmetric pair associated with a screened metallic environment, and one broader, more symmetric pair corresponding to an unscreened environment. [40][41][42] Here, we also associated the Mo 4+ state to 2 sets of doublets with their Mo 3d5/2 peaks located at ca. 229.3 and 230.6 eV.…”
Section: Nap-xps Measurementsmentioning
confidence: 99%
“…Mo is earth abundant and has a similar electronic structure to Cr. Oxides, carbides, and nitrides of molybdenum have thus been widely utilized in catalytic applications, which but are not limited to alkene isomerization, hydrogenation, hydrogenolysis, and hydrodesulfurization. In contrast, as a candidate for catalytic dehydrogenation, Mo-based catalyst has been mainly studied in oxidative dehydrogenation of ethane, propane, and n -butane in previous studies. , For example, the catalytic performances of molybdenum oxides, including MoO 3 crystallites, MoO x monomers, or polymers, are typically affected by the supporting species, the molybdenum oxidation state, and the dispersion of the metals. Wang and co-workers showed that the Mo/MgAl 2 O 4 catalyst can achieve ca.…”
Section: Introductionmentioning
confidence: 99%